(untitled) (Nepal Journal of Epidemiology, 2018)
The growth of motorised and mass transportation has improved the lives and lifestyles of many. This economic progress has major drawbacks including: increased air pollution, road traffic crashes/injuries (RTCs/RTIs). Some papers may refer to Road Traffic Accidents or RTAs, but experts recommend the more appropriate to use RTIs. In recent decades the proportion of RTI to all deaths has declined in high-income countries whereas it has risen in many low- and middle-income countries.